DECOLORIZATION OF METHYL ORANGE DYE FROM SYNTHETIC WASTEWATER USING BIOSYNTHESIZED IRON NANOPARTICLES - ELAVARASI .N,; GOMATHI PRIYA .P, (International Journal of Pharma and Bio Sciences, 2015)
The present study reports the synthesis of iron nanoparticles of biological (Azadiracta indica leaf extract) and chemical (sodium borohydride) methods. The nanoparticles were characterized by UV-visible spectroscopy, HR-SEM (High Resolution Scanning Electron Microscopy) and EDX (Energy Dispersive X-ray) spectroscopy. The HR-SEM images of biologically synthesized iron nanoparticles (BFeNPs) and chemically synthesized iron nanoparticles (CFeNPs) indicate that the BFeNPs were mostly spherical and uniform in size with an average diameter of about 28 nm and the CFeNPs were irregular in shape with an average diameter of about 52 nm. The EDAX spectrum data show the nanoparticles are primarily composed of iron and iron oxide. The efficiency of green synthesized iron nanoparticles is compared with CFeNPs with hydrogen peroxide in the degradation of methyl orange. Based on the kinetic studies and FTIR analysis, it was concluded that BFeNPs demonstrated more effective capability for the dye degradation both in terms of the extent and speed of dye removal compared with CFeNPs.